Rancang Bangun Website Media Pembelajaran Di Smp Katolik Santa Maria Palangkaraya Dengan Php Mysql - Widiatry, Widiatry; Kristina, Dhea (Journal of Information Technology and Computer Science, 2022)
Santa Maria Catholic Middle School is a junior high school which is located at Jalan Cilik Riwut, Jekan Raya District, Palangka Raya City. It does not yet have a website like most schools in Palangkaraya City. So this Junior High School does not introduce its school to the wider community. Not only that, this junior high school also still uses the books offered by the teacher for its learning. Based on this background, "Design and Build a Learning Media Website at Santa Maria Palangkaraya Catholic Middle School with PHP MySQL", in order to support the student learning process. The methodology used in designing and building this website is the waterfall method, namely analysis, design, implementation and testing. The design design uses Data Flow Diagrams (DFD), Flowcharts, ERD, coding using PHP and MySQL and Black Box Testing as a software testing method. From the results of this test it can be concluded that "Designing Learning Media Websites at Santa Palangkaraya Catholic Middle School with PHP MySQL" was created with the aim of facilitating student learning.